A longitudinal study of the cause and consequences of changes in diversification in the U.S. pharmaceutical industry 1977–1986 - Hill, Charles W. L.; Hansen, Gary S. (Strategic Management Journal, 1991)
Abstract The paper hypothesizes that diversification by firms based in the pharmaceutical industry during the 1977‐86 time period was primarily undertaken to reduce the risks associated with being dependent upon a technologically dynamic environment. Consistent with this non‐efficiency motive for diversification, declining economic performance is predicted. A longitudinal empirical analysis provides support for these propositions.